Benefit of Bevacizumab-Based Frontline Therapy in Patients with Metastatic Colorectal Cancer (mCRC): a Turkish Oncology Group Study - (:unkn) unknown (Humana Press Inc., 2016)
Background: Several chemotherapy regimens using bevacizumab have been developed. Our goal was to investigate regimens that have demonstrated significant clinical activity in patients with metastatic colorectal cancer (mCRC). Materials and Methods: Six hundred and sixty six patients with mCRC who received first-line chemotherapy combination with bevacizumab were studied. Fluoropyrimidine (F) plus irinotecan (I)-based (FI-bev), F plus oxaliplatin (O)-based (FO-bev), and F-based (F-bev) treatment regimens were compared with respect to progression-free survival (PFS) and overall survival (OS). Results: The median PFS of FI-bev (n = 414) was 10.9 months (95 % CI 10–11.8), of FO-bev (n = 211) was 9.4 months (95 % CI 8.3–10.4), and of F-bev (n = 41) was 9.5 months (95 % CI 5.9–13.1) (p = 0.089). The median OS of FI-bev was 26.3 months (95 % CI 21.7–30.9), of FO-bev was 27 months (95 % CI 24.3–29.7), and of F-bev was 23.3 months (95 % CI 12.7–33.9) (p = 0.102). In KRAS wild-type patients, the median PFS of FI-bev group was significantly longer than FO-bev group (10.5 vs. 9.1 months, p = 0.006). The FI-bev group had better OS than FO-bev group with borderline significance (p = 0.058). The FI-bev group had significantly longer OS than F-bev group. Patients who underwent metastasectomy or those with Eastern Cooperative Oncology Group performance status (ECOG-PS) ≤1 had longer PFS and OS independent of the type of chemotherapy regimen. Conclusion: FI-bev may be the preferred frontline regimen for patients with KRAS wild-type mCRC. Metastasectomy and performance score were the strongest positive predictors of OS and PFS regardless of backbone chemotherapy regimen. © 2016, Springer Science+Business Media New York.
Keywords: Fluoropyrimidine plus bevacizumab; Irinotecan plus bevacizumab; Metastatic colorectal cancer; Oxaliplatin plus bevacizumab